Molecular paleontology of transposable elements in the Drosophila melanogaster genome - Kapitonov, Vladimir V. (National Academy of Sciences, 2003)
We report here a superfamily of “cut and paste” DNA transposons called Transib. These transposons populate the Drosophila melanogaster and Anopheles gambiae genomes, use a transposase that is not similar to any known proteins, and are characterized by 5-bp target site duplications. We found that the fly genome, which was thought to be colonized by the P element <100 years ago, harbors ≈5 million year (Myr)-old fossils of ProtoP, an ancient ancestor of the P element. We also show that Hoppel, a previously reported transposable element (TE), is a nonautonomous derivate of ProtoP. We found that the “rolling-circle” Helitron transposons identified previously in plants and worms populate also insect genomes. Our results indicate that Helitrons were horizontally transferred into the fly or/and mosquito genomes. We have also identified a most abundant TE in the fly genome, DNAREP1_DM, which is an ≈10-Myr-old footprint of a Penelope-like retrotransposon. We estimated that TEs are three times more abundant than reported previously, making up ≈22% of the whole genome. The chromosomal and age distributions of TEs in D. melanogaster are very similar to those in Arabidopsis thaliana. Both genomes contain only relatively young TEs (<20 Myr old), constituting a main component of paracentromeric regions.